LED degradation: From component to system. (September 2016) - Hamon, B.; van Driel, W.D.
Abstract: Human civilization revolves around artificial light. Since its earliest incarnation as firelight to its most recent as electric light, artificial light is at the core of our existence. It has freed us from the temporal and spatial constraints of daylight by allowing us to function equally well night and day, indoors and outdoors. It evolved from open fire, candles, carbon arc lamp, incandescent lamp, fluorescent lamp to what is now on our door step: solid state lighting (SSL). SSL refers to a type of lighting that uses semiconductor light-emitting diodes (LEDs), organic or polymer light-emitting diodes (OLED/PLED) as sources of illumination rather than electrical filaments, plasma (used in arc lamps such as fluorescent lamps), or gas. SSL applications are now at the doorstep of massive market entry into our offices and homes. This penetration is mainly due to the promise of an increased reliability with an energy saving opportunity: a low cost reliable solution. An SSL system is composed of a LED engine with a micro-electronics driver(s), integrated in a housing that also provides the optical, sensing and other functions. Knowledge of (system) reliability is crucial for not only the business success of the future SSL applications, but also solving many associated scientific challenges. In practice, a malfunction of the system might be induced by the failure and/or degradation of the subsystems/interfaces. This paper will address the items to ensure high reliability of SSL systems by describing LED degradation from a component and a system perspective. Highlights: How to ensure high reliability of SSL systems by describing LED degradation from a component and a system perspective. SSL reliability is a challenging task, mainly due to: The large amount of unknown failure modes and mechanisms, and lack of field data. The technological gap to physically describe these mechanisms. Non-existing optimal acceleration test methods and/or standards. The requested high lifetime levels.